Neutrophils as Trojan Horse vehicles for Brucella abortus macrophage infection - Gutiérrez-Jiménez, Cristina (2019)
Brucella abortus is a stealthy intracellular bacterial pathogen of animals and humans. This bacterium promotes the premature cell death of neutrophils (PMN) and resists the killing action of these leukocytes. B. abortus-infected PMNs presented phosphatidylserine (PS) as "eat me" signal on the cell surface. This signal promoted direct contacts between PMNs and macrophages (Mϕs) and favored the phagocytosis of the infected dying PMNs. Once inside Mϕs, B. abortus replicated within Mϕs at significantly higher numbers than when Mϕs were infected with bacteria alone. The high levels of the regulatory IL-10 and the lower levels of proinflammatory TNF-α released by the B. abortus-PMN infected Mϕs, at the initial stages of the infection, suggested a non-phlogistic phagocytosis mechanism. Thereafter, the levels of proinflammatory cytokines increased in the B. abortus-PMN-infected Mϕs. Still, the efficient bacterial replication proceeded, regardless of the cytokine levels and Mϕ type. Blockage of PS with Annexin V on the surface of B. abortus-infected PMNs hindered their contact with Mϕs and hampered the association, internalization, and replication of B. abortus within these cells. We propose that B. abortus infected PMNs serve as "Trojan horse" vehicles for the efficient dispersion and replication of the bacterium within the host.